Predicting Factors of Interpersonal and Situational Influences for Performing Stretching Exercises Based on Pender’s Model - Delshad, Mohammad Hossein; Tavafian, Sedigheh Sadat; Kazemnejad, Anoshirvan (Nurse Media Journal of Nursing, 2019)
Background: Physical activity affects office employees in achieving a healthy lifestyle and preventing diseases such as Musculoskeletal Diseases (MSDS). Combining sports such as stretching exercises in healthy lifestyle programs is one of the most important decisions to prevent such disease.Purpose: This study aimed to predict factors of interpersonal and situational influences for stretching exercise (SE) among office employees at Shahid Beheshti University of Medical Sciences.Methods: A cross-sectional study was conducted among 420 office employees recruited by multi-stage cluster sampling. Self-administered questionnaires of SE and interpersonal and situational influences based on Pender’s Health Promotion Model, as well as socio-demographic data, were used in this study. The collected data were analyzed using Spearman correlation and logistic regression tests.Results: Results showed that among 420 participants, the scores of interpersonal and situational influences, and SE were 4.6±11.52, 4.5±14.21, and 2.48±17.64, respectively. There was a significant relationship between interpersonal influence and SE (r=0.54; p<0.05), and undergoing treatment and SE (r=0.77; p<0.05). There was no relationship between situational influence and SE (r=0.107; p>0.05), and interpersonal influences were a strong predictor for SE behavior.Conclusion: This study showed that the office employees who were more interpersonal influencers were more likely to do stretching exercise behavior. Therefore, interpersonal factors could be used as an educational principle in facilitating admission behavior of SE regarding Pender’s Model.